2023
DOI: 10.1038/s41598-023-29265-w
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the impact of temperature and oxygen partial pressure on the spent nuclear fuel oxidation during its dry management

Abstract: The management of Spent Nuclear Fuel (SNF) comprises different stages in which security is demonstrated. Nevertheless, fundamental research can lead to other design options that must be considered. Currently, one of the focuses is the dry interim storage option, as the shortest-term solution until final repositories are available. During this stage, one concern is the oxidation of the fuel. If UO2 (SNF matrix) is exposed to air at high-enough temperature, formation of U3O8 takes place. The larger volume of thi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 49 publications
(102 reference statements)
0
1
0
Order By: Relevance
“…An SNF storage canister represents an ideal test specimen for this study because it is far too large for movement or direct pro lometry measurements, but it has been shown that surface roughness plays an important role in particulate deposition [16][17][18] and pitting susceptibility [19][20][21] . Therefore, understanding the variation in surface roughness across various features can provide important information for canister ageing management programs and ensure fuel integrity 22 .…”
Section: Introductionmentioning
confidence: 99%
“…An SNF storage canister represents an ideal test specimen for this study because it is far too large for movement or direct pro lometry measurements, but it has been shown that surface roughness plays an important role in particulate deposition [16][17][18] and pitting susceptibility [19][20][21] . Therefore, understanding the variation in surface roughness across various features can provide important information for canister ageing management programs and ensure fuel integrity 22 .…”
Section: Introductionmentioning
confidence: 99%